2009
DOI: 10.1111/j.1600-6143.2009.02550.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Anti-TNFα Treatment in a Child with Posttransplant Recurrent Focal Segmental Glomerulosclerosis

Abstract: Posttransplant recurrence of focal and segmental glomulosclerosis (FSGS) occurs in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 16 publications
0
25
0
1
Order By: Relevance
“…Predictable recognition of this group might therefore facilitate accurate prognosis as well as identification of which patients to target for more intense therapy pretransplant, with strict emphasis on better control of nephrotic relapses earlier in their course of disease to avoid secondary steroid resistance. Therapy is also currently limited by a lack of consensus for the optimal management of post-transplant SRNS recurrence, such as ciclosporin versus tacrolimus, peritransplant plasmapheresis, rituximab (anti-CD20), 32 or infliximab/eternacept (anti-TNFa), 33 all strategies that have been used in attempts to control post-transplant disease with varying success.…”
Section: Discussionmentioning
confidence: 99%
“…Predictable recognition of this group might therefore facilitate accurate prognosis as well as identification of which patients to target for more intense therapy pretransplant, with strict emphasis on better control of nephrotic relapses earlier in their course of disease to avoid secondary steroid resistance. Therapy is also currently limited by a lack of consensus for the optimal management of post-transplant SRNS recurrence, such as ciclosporin versus tacrolimus, peritransplant plasmapheresis, rituximab (anti-CD20), 32 or infliximab/eternacept (anti-TNFa), 33 all strategies that have been used in attempts to control post-transplant disease with varying success.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-TNF-a agents Leroy et al [69] Infliximab (3 mg/kg twice monthly) [70] Etanercept (twice weekly) 1 patient (< 18 yr) Partial remission Rituximab ® Pescovitz et al [28] Rituximab ® (6 doses, 375 mg/m 2 ) 1 patient (< 18 yr) Complete remission Hristea et al [74] Complete remission in 3; partial remission in 2; no response in 1 1/7 patients received one dose, 4/7 patients received 2 doses, and 1/7 received 4 doses; 1/7 patients experienced a severe reaction during first infusion and was excluded from the analysis Tsagalis et al [79] Rituximab ® (1 g, 2 doses) + PE 4 patients (2 < 18 yr; 2 ≥ 18 yr)…”
Section: Messina M Et Al Focal Segmental Glomerulosclerosis In Renamentioning
confidence: 99%
“…At the present time, very few cases of FSGS have been treated with anti-TNF-a agents. Leroy et al [69] reported a favorable outcome (complete remission) for a 15-year-old patient with recurrent FSGS that was presumably resistant to other treatments (increased immunosuppressant dose, PE, intravenous immunoglobulin, high dose steroids, CyA, and CYC) after administration of an anti-TNF-a blocker (firstly infliximab, then etanercept). Bitzan et al [70] showed that plasmapheresis effluent or fresh plasma (obtained from a child with recurrent FSGS and from two children with primary FSGS) caused cytoskeleton disturbance on podocyte culture.…”
Section: Anti-tumor Necrosis Factor-alpha Agentsmentioning
confidence: 99%
“…He finally went into remission with infliximab. In 2009, Leroy et al [7] reported an interesting case. They encountered a boy with focal segmental glomerular sclerosis who relapsed after renal transplantation.…”
Section: Discussionmentioning
confidence: 97%